2014
DOI: 10.1159/000362155
|View full text |Cite
|
Sign up to set email alerts
|

Is Brain Natriuretic Peptide a Reliable Biomarker of Hydration Status in All Peritoneal Dialysis Patients?

Abstract: Background: Achievement of euvolemia is a fundamental challenge in the peritoneal dialysis (PD) population. Bioimpedance spectroscopy (BIS) is one of the best techniques for routine assessment of hydration status (HS) in PD, but in recent years, the role of brain natriuretic peptides (BNP) in the assessment of volume status has gained interest. The aim of this study was to investigate the relation between BNP and volume status as measured by BIS in PD patients and to assess how these variables correlate accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…23 As such, our results suggested that myocardial wall stress was reduced in dogs with tick paralysis, regardless of their state of respiratory compromise. [42][43][44][45][46] Future studies could investigate the presence or absence of significant dehydration in dogs with tick paralysis using additional indicators of hydration status such as urine specific gravity and total serum protein concentration, 47 and body weight at admission and after recovery. Furthermore, many dogs with tick paralysis vomit or regurgitate, possibly also contributing to a reduction in preload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 As such, our results suggested that myocardial wall stress was reduced in dogs with tick paralysis, regardless of their state of respiratory compromise. [42][43][44][45][46] Future studies could investigate the presence or absence of significant dehydration in dogs with tick paralysis using additional indicators of hydration status such as urine specific gravity and total serum protein concentration, 47 and body weight at admission and after recovery. Furthermore, many dogs with tick paralysis vomit or regurgitate, possibly also contributing to a reduction in preload.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in dogs and a range of other species that dehydration in the acute setting similarly decreases plasma natriuretic peptide concentrations. [42][43][44][45][46] Future studies could investigate the presence or absence of significant dehydration in dogs with tick paralysis using additional indicators of hydration status such as urine specific gravity and total serum protein concentration, 47 and body weight at admission and after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, BNP may be used to predict mortality and to guide fluid management in hemodialysis patients. 25,26 In our study, we chose BNP because of its short half-life and relative independence from the glomerular filtration rate and patient's age, compared to NT pro-BNP. 27,28 de Cal et al 29 report that increased BNP levels are associated with AKI development on ICU admission or during the ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Na avaliação dos exames bioquímicos, o único que apresentou diferença significativa entre os grupos foi o NT pró -BNP, pacientes HH apresentaram níveis mais elevados do mesmo, resultado semelhante foi encontrado por Kocyigit et al, (2014) e Crepaldi et al, (2014).…”
Section: Análise Estatísticaunclassified
“…A meia-vida mais longa de NT pró -BNP pode torná-lo um índice mais preciso da tensão ventricular e, consequentemente, um melhor indicador de prognóstico ao compará-lo com o BNP. Outros exames como o ecocardiograma devem ser utilizados para avaliar as alterações cardíacas (CREPALDI et al, 2014). (BIESEN, et al, 2011;CADER et al, 2013;FERNANDEZ et al, 2013,).…”
Section: Análise Estatísticaunclassified